2010
DOI: 10.1177/0022057410190001-204
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Instruction in Early Childhood Education: Early Literacy as a Microcosm of Shifting Perspectives

Abstract: Not everything that counts can be counted. And not everything that can be counted counts. -Attributed to Albert EinsteinDetermining what counts, and what does not, as evidence of young children's development has become an increasingly complex issue for early childhood educators. A broad range of stakeholders in the education of young children, from parents and teachers to administrators and policy-makers, have their own views about how children develop and how learning should be supported and assessed in Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In addition, these curricula are currently expected to deliver results not only in the general areas of child development but also in foundational academic competencies. With the academic (mostly ‘constrained’) skills more amenable to change short-term ( Casbergue, 2010 ; McCormick et al, 2021 ), play-based curricula often find themselves at a disadvantage compared to skill-based curricula when children get assessed on discrete academic skills only. Unfortunately, it is becoming harder and harder to use previous studies, including the classic Perry Preschool study ( Schweinhart, 2019 ), in defense of play-based programs because of the changes in school readiness expectations.…”
Section: Locating Play In the Space Of Sel Interventionsmentioning
confidence: 99%
“…In addition, these curricula are currently expected to deliver results not only in the general areas of child development but also in foundational academic competencies. With the academic (mostly ‘constrained’) skills more amenable to change short-term ( Casbergue, 2010 ; McCormick et al, 2021 ), play-based curricula often find themselves at a disadvantage compared to skill-based curricula when children get assessed on discrete academic skills only. Unfortunately, it is becoming harder and harder to use previous studies, including the classic Perry Preschool study ( Schweinhart, 2019 ), in defense of play-based programs because of the changes in school readiness expectations.…”
Section: Locating Play In the Space Of Sel Interventionsmentioning
confidence: 99%
“…Early reading and math are the only emphases of certain school readiness assessments, whilst other tests emphasize physical or social-emotional development (Daily et al, 2012). Early academic assessment frequently uses direct assessment, but developmental assessment frequently involves observation (Bradbury, 2014;Casbergue, 2011). However, research has indicated that when determining a child's readiness for school, a whole-child approach that takes into account both academic and developmental skills may be the most effective (Daily et al, 2012;Davoudzadeh et al, 2015;Yoon, 2015).…”
Section: Introductionmentioning
confidence: 99%